2021
DOI: 10.3390/met11101605
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Threshold Switching and Bipolar Resistive Switching in Ag/SnOx/TiN Memory Device

Abstract: In this work, we observed the duality of threshold switching and non-volatile memory switching of Ag/SnOx/TiN memory devices by controlling the compliance current (CC) or pulse amplitude. The insulator thickness and chemical analysis of the device stack were confirmed by transmission electron microscope (TEM) images of the Ag/SnOx/TiN stack and X-ray photoelectron spectroscopy (XPS) of the SnOx film. The threshold switching was achieved at low CC (50 μA), showing volatile resistive switching. Optimal CC (5 mA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Unlike conventional SnO X , which demands an annealing process to achieve resistive switching (RS) characteristics, the as-deposited SnO X used in this paper showed RS characteristics. As-deposited SnO X by direct current (DC) reactive magnetron sputtering has already been verified the RS in a Ag/SnO X /ITO device by Da chen and Shi-Hua Huang, and it showed a low resistance of less than 3 kΩ and a resistance window of less than ~10 [ 13 , 14 ]. In addition, Jidong Jin et al reported that the DC-sputtered SnO X showed poor RS on the stack of an Al/SnO X /Pt device [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike conventional SnO X , which demands an annealing process to achieve resistive switching (RS) characteristics, the as-deposited SnO X used in this paper showed RS characteristics. As-deposited SnO X by direct current (DC) reactive magnetron sputtering has already been verified the RS in a Ag/SnO X /ITO device by Da chen and Shi-Hua Huang, and it showed a low resistance of less than 3 kΩ and a resistance window of less than ~10 [ 13 , 14 ]. In addition, Jidong Jin et al reported that the DC-sputtered SnO X showed poor RS on the stack of an Al/SnO X /Pt device [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…38 Such switching behavior where the device switches from HRS to LRS during the forward sweep and again switches from LRS to HRS during the reverse sweep at the same polarity is known as Threshold Switching (TS). [39][40][41][42][43] TS devices may be useful to resolve the sneak path problem in memory applications having crossbar array structure as a selector device. 40 Similar behavior was also observed in case of negative polarity, where threshold voltage (V Th ) was −1.636 V and holding voltage (V h ) was −1.437 V.…”
Section: Resultsmentioning
confidence: 99%
“…Those ions drift according to the direction of the electric field and determine the states of the device. The RS behavior of as-deposited SnO X formed through sputter has already been proven in the literature [ 12 , 13 , 14 , 15 , 16 ], but better RS characteristics can be achieved using DC-sputtering without the assistance of the annealing process.…”
Section: Introductionmentioning
confidence: 99%